Association of Residual Feed Intake With Blood Metabolites and Reproduction in Holstein Cows - Nehme Marinho, Mariana; Santos, José E. P. (Frontiers in Animal Science, 2022)
The objectives of this study were to evaluate the associations between residual dry matter (DM) intake or residual feed intake (RFI) from 1 to 15 weeks postpartum and concentrations of metabolites in plasma in early lactation and reproduction in Holstein cows. Data from 9 experiments, including 851 cows, were used. Intake of DM, milk yield, and body weight were evaluated daily, whereas milk composition and body condition were evaluated twice weekly for the first 105 days postpartum. Blood was sampled on the day of calving and again on days 7, 14, and 21 postpartum and analyzed for concentrations of non-esterified fatty acids (FA), β-hydroxybutyrate (BHB), and glucose. Reproduction was evaluated for the first 300 days postpartum. Residual DM intake was calculated as the observed minus the predicted intake, with intake predicted based on a model that accounted for major energy sinks. Cows were ranked and categorized into RFI quartiles, from the smallest (Q1) to the largest (Q4) RFI (−1.87, −0.46, 0.39, and 1.90 kg/day). Increasing efficiency (i.e., from Q4 to Q1) resulted in linear decreases in DM intake (Q1 to Q4; 18.9, 20.4, 21.3, and 22.7 kg/day), and median days open (132, 125, 135, and 147 d). Conversely, improving efficiency was associated with a linear increase in pregnancy per artificial insemination (AI, 31.4, 30.6, 31.2, and 24.5%) and quadratic increases in the 21-day cycle pregnancy rate (21.2, 21.1, 22.0, and 16.6%) and the proportion of pregnant cows (79.0, 80.7, 82.4, and 71.5%). The estimated net energy for lactation (NEL) content of diets increased linearly with improved RFI (1.88, 1.76, 1.71, and 1.58 Mcal/kg), resulting in no association between RFI and energy-corrected milk yield or body energy change. Nevertheless, increased feed efficiency was associated with a linear increase in concentrations of blood FA (0.68, 0.63, 0.60, and 0.59 mM), but a quadratic association with BHB (0.75, 0.64, 0.64, and 0.65 mM), with no association with glucose. Collectively, the most feed efficient cows ate 3.8 kg/day less DM, produced the same amount of energy-corrected milk, and had improved reproductive performance compared with the least efficient cows, thus suggesting that the underlying mechanisms responsible for improved feed efficiency might also be linked with improvements in reproduction.